Evaluation of the Antiproliferative Activity of the Leaves from Arctium lappa by a Bioassay-Guided Fractionation - Celso Vataru Nakamura; João Carlos Palazzo de Mello; Tânia Ueda-Nakamura; Cláudio Roberto Novello; Ivânia Teresinha Albrecht Schuquel; Cássia Mônica Sakuragui; Heinrich Luftmann; Samara Requena Nocchi; Karine Zanoli; Rafael Eidi Yamamoto; Fabio Bahls Machado (Molecules, 2012)
Arctium lappa L. (Asteraceae) is used in folk medicine around the World, and shows several kinds of biological activity, particularly in vitro antitumor activity in different cell lines. This study evaluated the antiproliferative activity of the crude extract, semipurified fractions, and isolated compounds from the leaves of A. lappa, through bioassay-guided testing in Caco-2 cells. The crude extract was obtained with a 50% hydroethanolic extract and then partitioned with hexane, ethyl acetate, and n-butanol. The ethyl-acetate fraction (EAF) showed antiproliferative activity. This fraction was subjected to sequential column chromatography over silica gel to afford onopordopicrin (1), mixtures of 1 with dehydromelitensin-8-(4'-hydroxymethacrylate) (2), a mixture of 2 with dehydromelitensin (3), mixture of 1 with melitensin (4), dehydrovomifoliol (5), and loliolide (6). The compounds were identified by spectroscopic methods (NMR, MS) and comparison with literature data. This is the first description of compounds 2–5 from this species. The compounds tested in Caco-2 cells showed the following CC50 (µg/mL) values: 1: 19.7 ± 3.4, 1 with 2: 24.6 ± 1.5, 2 with 3: 27 ± 11.7, 1 with 4: 42 ± 13.1, 6 30 ± 6.2; compound 5 showed no activity.